2017
DOI: 10.1039/c6ra27518d
|View full text |Cite
|
Sign up to set email alerts
|

A novel random terpolymer for high-efficiency bulk-heterojunction polymer solar cells

Abstract: A new random terpolymer, coded LGC-D013, based on TPD as the acceptor and BDT and terthiophene as the donor units, has been synthesized and characterized for donor material in bulk-heterojunction (BHJ) organic photovoltaic (OPV) application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Moreover, the π–π stacking distances of the blended films are calculated to be (3.86, 3.81, and 3.77) Å for the Pristine, DIO, and DIO/Annealing, respectively. These results clearly indicate that slot‐die coated films with additive and thermal annealing treatments decrease the π–π stacking distance of face‐on orientation, leading to highly improved intermolecular interaction and charge transport in the blended film, and thus resulting in high J sc , FF, and PCE. For better understanding of the enhanced PSC‐performances with slot‐die coating, the nanoscale‐morphology of the printed ternary‐blend films was studied using atomic force microscopy (AFM), as presented in Figure d–f.…”
Section: Representative Photovoltaic Parameters Of the Ptb7‐th:pc71bmsupporting
confidence: 76%
“…Moreover, the π–π stacking distances of the blended films are calculated to be (3.86, 3.81, and 3.77) Å for the Pristine, DIO, and DIO/Annealing, respectively. These results clearly indicate that slot‐die coated films with additive and thermal annealing treatments decrease the π–π stacking distance of face‐on orientation, leading to highly improved intermolecular interaction and charge transport in the blended film, and thus resulting in high J sc , FF, and PCE. For better understanding of the enhanced PSC‐performances with slot‐die coating, the nanoscale‐morphology of the printed ternary‐blend films was studied using atomic force microscopy (AFM), as presented in Figure d–f.…”
Section: Representative Photovoltaic Parameters Of the Ptb7‐th:pc71bmsupporting
confidence: 76%
“…Moreover, the similar designing strategy for TPD‐based terpolymers was also reported by Na and co‐workers. To achieve highly ordered crystallinity, they used linear block terthiophene unit to partly substitute 2D monomer BDT in BDT‐TPD conjugated copolymer . The resulted random terpolymer TD25 exhibited strong and regular crystalline structure after DIO treatment, leading to an improvement in both μ h and μ e with 1—2 orders higher than those of the as‐cast films.…”
Section: Efficient Terpolymer Donors With Representative Building Blocksmentioning
confidence: 99%
“…In both acceptor types, P28 outperformed due to its enhanced optical absorption and fine-tuned electrochemical and morphological properties. Another versatile aromatic structure molecular with two imide functional groups, easy synthesis and provides structural flexibility is TPD (Zou et al, 2010;Bang et al, 2017; Heo et al, 2018). Terpolymers based on TPD molecular unit have been reported.…”
Section: Benzodithiophenedione (Bdd) and Thienopyrroledione (Tpd) Rinmentioning
confidence: 99%
“…Terpolymers based on TPD molecular unit have been reported. Bang et al (2017) reported a terpolymer based on TPD, BDT and terthiophene molecular structures in a 50, 25, and 25% mixing molar ratio of the monomers, respectively (P31) (Figure 4). It showed broad optical absorption (300-700 nm) and a band gap of 1.84 eV.…”
Section: Benzodithiophenedione (Bdd) and Thienopyrroledione (Tpd) Rinmentioning
confidence: 99%